1997
DOI: 10.1111/j.1469-7793.1997.031bl.x
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of extracellular Ca2+ receptor‐stimulated hormone release from sheep thyroid parafollicular cells

Abstract: 1. Expression of receptors to extracellular calcium enables parafollicular cells of the thyroid gland (PF cells) to release calcitonin (CT) and serotonin (5_HT) in response to increased external Ca¥. Recently, a calcium-sensing receptor (CaR), similar to the G protein-coupled receptor for external Ca¥ cloned from parathyroid gland, was shown to be expressed in PF cells. Using a highly purified preparation of sheep PF cells, we have examined the electrical and biochemical processes coupling CaR activation to ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
69
0
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 109 publications
(71 citation statements)
references
References 52 publications
(68 reference statements)
1
69
0
1
Order By: Relevance
“…PKC, however, appears to play an important role in the secretory process. Phorbol esters stimulate 5-HT secretion, and secretion in response to phorbol esters is abolished by phorbol ester downregulation of PKC (Tamir et al, 1990;McGehee et al, 1997). Nevertheless, despite the ability of phorbol ester downregulation of PKC to block phorbol ester-induced secretion, downregulation only slightly inhibits 5-HT secretion when it is evoked by 1[Ca 2ϩ ] e .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…PKC, however, appears to play an important role in the secretory process. Phorbol esters stimulate 5-HT secretion, and secretion in response to phorbol esters is abolished by phorbol ester downregulation of PKC (Tamir et al, 1990;McGehee et al, 1997). Nevertheless, despite the ability of phorbol ester downregulation of PKC to block phorbol ester-induced secretion, downregulation only slightly inhibits 5-HT secretion when it is evoked by 1[Ca 2ϩ ] e .…”
mentioning
confidence: 99%
“…The CaR is G-protein-coupled (Herbert and Brown, 1995;Ruat et al, 1996) and has been demonstrated to be linked to Gi and Gq (Tamir et al, 1996). After the activation of the CaR by 1[Ca 2ϩ ] e , PF cells depolarize (as a result of an increase in a nonselective plasma membrane cation conductance) (McGehee et al, 1997), secretory vesicles acidify (Tamir et al, 1994b), and 5-HT is secreted (Tamir et al, 1990(Tamir et al, , 1994bMcGehee et al, 1997).…”
mentioning
confidence: 99%
“…Much has been learned from studies of lingual nutrient detection due to identification of the G protein family, which couples with nutrient-sensitive G protein coupled receptors located in the taste buds on the tongue and in the intestine (26,27). The CaR, a G protein-coupled receptor, is best known and understood for its control of PTH synthesis and secretion in response to changes in Ca, Mg, Sr, and La (17,18). CaRs are distributed along most of the gastrointestinal tract, from the stomach to the large intestine (23,28).…”
Section: Discussionmentioning
confidence: 99%
“…CaRs are distributed along most of the gastrointestinal tract, from the stomach to the large intestine (23,28). The physiologic role of CaRs is the maintenance of constant blood Ca 2 + levels (1.1-1.3 mM) through continuous adjustments of PTH release from the parathyroid chief cells, which are highly sensitive to the slightest changes in extracellular Ca ion concentrations (17,18). In the present study, we showed that Mg, La, or Sr, which are CaR agonists, can partially substitute for dietary Ca.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation